Hydrogen isotope exchange in tungsten during annealing in hydrogen atmosphere. (9th January 2019) - Ahlgren, T.; Jalkanen, P.; Mizohata, K.; Tuboltsev, V.; Räisänen, J.; Heinola, K.; Tikkanen, P.
Abstract: The radiological safety of the future thermonuclear fusion devices depends critically on the total tritium inventory in the plasma-facing components. The planned method to remove tritium from the ITER reactor tungsten divertor is to perform vacuum baking. We show that tritium removal from tungsten can be enhanced by the isotope exchange mechanism by doing the baking in H atmosphere. The results show that the retained deuterium from 30 keV implantation can be expected to drop almost to zero after 24 h annealing at 250 °C in H atmosphere. Annealing in vacuum requires temperatures above 400 °C for close to zero retention.